Case Report: The Effect of Ajwa Date Consumption on Total Cholesterol Levels in Perimenopausal Women - Hamsah, M.; Aman, Abadi; Mappaware, Nasrudin Andi; Fujiko, Masita; Royani, Ida; Fortuna, Andi Cita Nadya (Journal La Medihealtico, 2024)
Based on the 2016 Riskesdas, the prevalence of high cholesterol in Indonesia among women aged 35-59 years was 52.9%, and among those aged ≥60 years, it was 58.7%. According to provincial data, the highest percentage of patients with high cholesterol levels at Posbindu and FKTP in Indonesia was in West Papua Province, reaching up to 70%. The concentration of cholesterol levels in women's blood tends to increase with age, particularly for those over 40 years old, due to hormonal factors, especially the decrease in estrogen production and function. The decline in estrogen levels leads to an increase in lipids or total cholesterol, resulting in changes in body fat composition associated with hypercholesterolemia. This case report aims to investigate the impact of consuming Ajwa dates on the total cholesterol levels of perimenopausal women. Results: Ajwa dates contain higher polyphenol concentrations with an impressive nutritional profile that enhances blood lipoproteins. Additionally, dates can increase estrogen levels due to the estradiol and estrone present in their pollen. Several experimental studies have shown a significant difference in total cholesterol levels in subjects before and after consuming Ajwa dates. Conclusion: There is a notable difference in total cholesterol levels before and after the administration of Ajwa dates.